Penghambat Kanal Kalsium sebagai Kontrol Glukosa Darah pada Insulinoma: Sebuah Laporan Kasus - Nizam, Nadhira; Putra, Ryan Tresna; Hasibuan, Anshari Saifuddin (UI Scholars Hub, 2025)
Insulinoma is a rare neuroendocrine tumor of the pancreas arising from β-cells, leading to excessive insulin secretion and resultant hypoglycaemia. Surgical resection is the first-line treatment for insulinoma, but when surgery is not feasible, medical therapy is an important option. Calcium channel blockers (CCBs) such as verapamil can inhibit insulin release from β-cells and have been proposed as an adjunct therapy to help control blood glucose levels in insulinoma. We report a 43-year-old man who presented to the emergency department with decreased consciousness due to hypoglycaemia. His capillary blood glucose at home was 35 mg/dL, about 8 hours after his last meal. He had a history of recurring hypoglycaemic episodes in the past month, with recorded blood glucose ranging from 26–100 mg/dL during a prior hospitalization. On examination, he was hemodynamically stable but had mild epigastric tenderness. Laboratory tests confirmed hyperinsulinemic hypoglycaemia (plasma glucose 58 mg/dL with concurrent serum insulin 47 µIU/mL and C-peptide 13.1 ng/mL), consistent with insulinoma. Abdominal imaging revealed a heterogeneous pancreatic mass suspected as an insulinoma. Initial management included a continuous infusion of 10% dextrose (500 mL/24h) with IV boluses of 40% dextrose as needed for blood glucose <70 mg/dL. Despite this, the patient experienced recurrent hypoglycaemia, so octreotide 50 µg three times daily was added. Octreotide alone did not fully stabilize his blood glucose levels. On the 6th day of hospitalization, oral verapamil 80 mg once daily was initiated – chosen both to treat the patient’s concurrent hypertension and for its potential to suppress insulin release. Following the addition of verapamil, the patient’s blood glucose levels improved and remained above 100 mg/dL with markedly reduced hypoglycemic episodes. The patient subsequently underwent a debulking surgery of the pancreatic tumor. This case highlights the importance of controlling blood glucose in insulinoma patients and demonstrates that the addition of verapamil can stabilize blood glucose when used alongside standard medical therapy (such as octreotide). Verapamil may serve as a useful adjunct in the management of insulinoma-related hypoglycemia, especially in patients awaiting surgery or those who are not surgical candidates.